Novel Metamaterials for Patch Antennas Applications - Zervos, T.; Lazarakis, F.; Alexandridis, A.; Dangakis, K.; Stamopoulos, D.; Pissas, M. (MOBILE LIGHTWEIGHT WIRELESS SYSTEMS, 2009)
In this paper we introduce the incorporation of magneto-electric materials into antenna design and the potential of controlling the behavior of the antenna by means of an external magnetic field. After an intensive study of magneto-electric material properties, a ferrimagnetic compound called Yttrium Iron Garnet (YIG) was found to be the best candidate for the novel antenna design. We provide a metamaterial patch antenna design where a part of the substrate is replaced by the YIG compound. After several design modifications the final model includes a circular-shaped YIG substrate just under the metallic patch and offers sufficient performance in terms of resonance, bandwidth and radiation efficiency. Additionally, in the presence of an external magnetic field the polarization becomes elliptical and the sense of the polarization (left or right) can be controlled through the direction of the magnetic field. That latter characteristic confirms the metamaterial-nature of the antenna.